Odpowiedzi

  • Użytkownik Zadane
2010-03-26T16:12:36+01:00
(-2 2/3) : 1,2 = -8/3 : 6/5 = -8/3 * 5/6 = -20/9 = -2 i 2/9
2/3:(-6)= 2/3 * (-1/6) = -1/9
(-0,45):1 4/5 = -45/100 : 9/5 = -9/20 * 5/9 = -1/4
(-2,75):(-2,2)= 1,25
(-3,5):(-1 2/5)= (-3,5) : (-1,4) = 2,5

Pozdrawiam:)
2010-03-26T17:04:18+01:00
(-2 2/3) : 1,2 = (-2 2/3) : 6/5 = ( - 8/3) * 5/6= -2 2/9


2/3:(-6)= 2/3 * (- 1/6)= - 1/9


(-0,45):1 4/5 =- 45/100 * 5/9= -1/4


(-2,75):(-2,2)= - 2 3/4 : (- 2 1/5)= - 11/4 * (-5/11) = 5/4= 1 1/5
(Parzysta liczba minusów, więc wynik jest liczbą dodatnią)

(-3,5):(-1 2/5)= - 3 1/2 : (-7/5)= - 7/2 * (-5/7)= 5/2 = 2 1/2

Jeślii pomogłam to się cieszę.. ; ]]
^^